Autophagy-targeted therapy to modulate age-related diseases: Success, pitfalls, and new directions - Waleska Kerllen Martins; Maryana do Nascimento da Silva; Kiran Pandey; Ikuko Maejima; Ercília Ramalho; Vania Claudia Olivon; Susana Nogueira Diniz; Daniel Grasso (Elsevier, 2021)
Autophagy is a critical metabolic process that supports homeostasis at a basal level and is dynamically regulated in response to various physiological and pathological processes. Autophagy has some etiologic implications that support certain pathological processes due to alterations in the lysosomal-degradative pathway. Some of the conditions related to autophagy play key roles in highly relevant human diseases, e.g., cardiovascular diseases (15.5%), malignant and other neoplasms (9.4%), and neurodegenerative conditions (3.7%). Despite advances in the discovery of new strategies to treat these age-related diseases, autophagy has emerged as a therapeutic option after preclinical and clinical studies. Here, we discuss the pitfalls and success in regulating autophagy initiation and its lysosome-dependent pathway to restore its homeostatic role and mediate therapeutic effects for cancer, neurodegenerative, and cardiac diseases. The main challenge for the development of autophagy regulators for clinical application is the lack of specificity of the repurposed drugs, due to the low pharmacological uniqueness of their target, including those that target the PI3K/AKT/mTOR and AMPK pathway. Then, future efforts must be conducted to deal with this scenery, including the disclosure of key components in the autophagy machinery that may intervene in its therapeutic regulation. Among all efforts, those focusing on the development of novel allosteric inhibitors against autophagy inducers, as well as those targeting autolysosomal function, and their integration into therapeutic regimens should remain a priority for the field.